Optimal design of a composite sandwich structure - Kovács György; Farkas József (Science and Engineering of Composite Materials, 2016)
This study shows the optimization method for a new complex structural model: laminated carbon fiber-reinforced plastic (CFRP) deck plates with polystyrene foam (EPS) inner core. The structure is designed for both minimal cost and minimal weight, taking into consideration the design constraints as follows: maximum deflection of the total structure, stress in the composite plates, stress in the polystyrene foam, eigenfrequency of the structure, thermal insulation of the structure, and size constraints for the design variables.